Benefits and pitfalls of GRACE data assimilation: A case study of terrestrial water storage depletion in India. Issue 9 (6th May 2017) - Girotto, Manuela; De Lannoy, Gabriëlle J. M.; Reichle, Rolf H.; Rodell, Matthew; Draper, Clara; Bhanja, Soumendra N.; Mukherjee, Abhijit
Abstract: This study investigates some of the benefits and drawbacks of assimilating terrestrial water storage (TWS) observations from the Gravity Recovery and Climate Experiment (GRACE) into a land surface model over India. GRACE observes TWS depletion associated with anthropogenic groundwater extraction in northwest India. The model, however, does not represent anthropogenic groundwater withdrawals and is not skillful in reproducing the interannual variability of groundwater. Assimilation of GRACE TWS introduces long‐term trends and improves the interannual variability in groundwater. But the assimilation also introduces a negative trend in simulated evapotranspiration, whereas in reality evapotranspiration is likely enhanced by irrigation, which is also unmodeled. Moreover, in situ measurements of shallow groundwater show no trend, suggesting that the trends are erroneously introduced by the assimilation into the modeled shallow groundwater, when in reality the groundwater is depleted in deeper aquifers. The results emphasize the importance of representing anthropogenic processes in land surface modeling and data assimilation systems. Key Points: GRACE observations of terrestrial water storage (TWS) in northwest India show trends likely associated with groundwater extraction Land models in global assimilation systems do not usually represent anthropogenic processes such as groundwater extraction and irrigation Assimilation of GRACE observations introduces realistic trends in TWS and groundwater along with an erroneous trend in evapotranspiration